A Systematic Review of the Potential for Promotion of Southern Epistemologies in Educational Research: Ubuntu Philosophy as a Research Paradigm, a Conceptual Model - Costa, King; Ntsobi, Mfanelo, Patrick (My University, 2023)
INTRODUCTION: The fast changing global trends, practices and ideologies have a potential to dissipate cultural identities of historically colonized nations, in favor for adoption of popularized perspectives. This problem is becoming more and more evident in South Africa due to urbanization and impact of globalization. However, this becomes a constant barrier in knowledge creation, development and management due to the fact that southern epistemologies remain pacified and under-utilized in scholarship and educational research. One such pacified epistemology in both social and educational research is Ubuntu. RESEARCH AIMS: The aim of this study is to determine the suitable application of Ubuntu philosophy in educational research. This will be achieved by answering a theoretical question: How can Ubuntu be adopted as a paradigm for research inquiries within a southern epistemological context? METHODS: The philosophy of Ubuntu is located within a subjective realist ontology. Applying non-intrusive research measures, a Scoping Review method was used to postulate evidence for adoption and application of Ubuntu philosophy as a research paradigm. Using a search engine comprising a number of social sciences databases (AnthroSource, ASSIA, Wilson Web and CSA), articles were appraised using the Systematic Review research protocols and analyzed using Critical Appraisal Skills Programme. The final activity for data analysis culminated into thematic analysis, using COSTA QDA technique. RESULTS: This study played a crucial role in magnifying the pacified voices of cultural epistemological contexts and existential realities. While the concept of Ubuntu is well researched across different disciplines, there was paucity of research on its adoption as a research paradigm and research design. The study found out that there were seminal works of established researchers on decoloniality and Afrocentrism, requesting consideration of Ubuntu as a research method. Thus, this scoping review found evidence that Ubuntu can and should be used as a research method in African contexts within social, economic and management sciences, as well as health and politics. CONCLUSION: It was concluded that institutions of higher learning should start teaching Ubuntu Action Research as a method of inquiry in their undergraduate and postgraduate research programmes. Consultants are also encouraged to investigate this research design approach for business and policy research.
Keywords: African; Afrocentric; Culture; Research Design; Ubuntu